The head and heart of news avoidance: How attitudes about the news media relate to levels of news consumption. (September 2022) - Edgerly, Stephanie
In today's media environment, there are increased opportunities to consume news in various formats and styles. Why then, do some people say they consume little to no news? The focus of this study is to identify the factors related to extremely low levels of news consumption. Survey data from a nationally representative sample of U.S. adults is used to test different explanations for news avoidance. Results point to several factors that explain lower overall levels of news consumption. Extremely low news consumption is related to a disinterest in politics, perceptions of news lacking relevance, low news self-efficacy and a lack of knowledge about the news system. Perhaps surprisingly, the emotional toll of news (e.g. news fatigue, upset feelings) did not explain variation in overall levels of news consumption. Based on these findings, efforts to convert news avoiders into more regular consumers of news is discussed.